Leadership, Organizational Readiness, and Management Strategies in the Implementation of Inclusive Education for Learners with Special Needs - Batang, Gemma (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the leadership practices of school heads in implementing inclusive education for learners with special needs in the City Schools Division of Calbayog. Anchored on Transformational Leadership Theory by Bass and Riggio (2006), Social System Theory by Luhmann (1995), and Social Constructivist Theory by Vygotsky (1978), the study aimed to determine the extent of leadership practices, organizational readiness, and management strategies employed in inclusive education. A descriptive-correlational research design was utilized, employing survey questionnaires as the primary research instrument administered to school heads and teachers involved in inclusive education programs. Statistical tools such as frequency counts, percentages, weighted mean, and correlation analysis were used to analyze the gathered data. Findings revealed that school heads demonstrated a high extent of leadership practices in strategic leadership, instructional support, professional development, stakeholder collaboration, and ethical leadership. Organizational readiness was also assessed to be moderate to high, particularly in terms of resource availability, teacher preparedness, and administrative support. Management strategies related to program implementation, capacity building, monitoring, and community partnerships were effectively practiced. The study further established significant relationships among leadership practices, organizational readiness, and management strategies, indicating that effective leadership and institutional preparedness contribute to the successful implementation of inclusive education for learners with special needs.
Keywords: Ethical Leadership; Inclusive Education; Instructional Support; Leadership Practices; Management Strategies; Organizational Readiness; Professional Development; Stakeholder Collaboration; Strategic Leadership; Transformational Leadership